Égalité entre les femmes et les hommes. Six niveaux pour comprendre et agir - Drion, Claudine (En question, 2016)
Le Monde selon les femmes, ONG belge de développement et Centre international de formation en genre, propose depuis plus de vingt ans des formations et des recherches-actions sur l’égalité entre les femmes et les hommes avec des associations partenaires du Sud.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; belgique; cours; discipline; droits des femmes*; europe; histoire et politique; inégalités; justice sociale; outils; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sex2283; sofia; systèmes d'oppressions; thématiques; travail social; trs1205

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social